Poison bonds - Rex Wang Renjie; Shuo Xia (Halle Institute for Economic Research (IWH), 2024)
This paper documents the rise of "poison bonds", which are corporate bonds that allow bondholders to demand immediate repayment in a change-of-control event. The share of poison bonds among new issues has grown substantially in recent years, from below 20% in the 90s to over 60% since mid-2000s. This increase is predominantly driven by investment-grade issues. We provide causal evidence that the pressure to eliminate poison pills has led firms to issue poison bonds as an alternative. Our analysis suggests that this practice entrenches incumbent managers and destroys shareholder value. Holding a portfolio of firms that remove poison pills but promptly issue poison bonds results in negative abnormal returns of -7.3% per year. Our findings have important implications for the agency theory of debt: (i) more debt may not discipline the management; and (ii) even without financial distress, managerial entrenchment can lead to agency conflicts between shareholders and creditors.
Keywords: 330; Abschottung des Managements; Agenturkosten für Schulden; Poison Pills; Poison Put; Schuldverträge